Iridium-zinc ultrathin nanosheet material as well as preparation method and application thereof
By using iridium zinc ultra-thin nanosheet material in the water decomposition anode oxygen-excitation electrode material to form atomic heterostructure and crystallization/amorphous phase interface, the poor activity and stability of the anode material in an acidic environment are solved, and efficient Kinetics and long-term stability of oxygen evolution reaction.
Patent Information
- Application Number
- CN202411442610.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing water-decomposed anode oxygen-excitation electrode materials have poor activity and stability in acidic environments, resulting in high hydrogen production costs and slow reaction kinetics.
Iridium zinc ultra-thin nanosheet material is used to form atomic heterostructure and crystallization/amorphous phase interface through zinc doping, which optimizes the electronic structure and reaction kinetics of the catalyst and improves oxygen evolution performance.
The oxygen evolution performance and stability are significantly improved. When the current density reaches 10mA cm-2, the oxygen evolution overpotential is only 271mV. The stability test has no significant attenuation after running for 115 hours, which is better than traditional materials.
Smart Images

Figure CN119287434A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials for producing hydrogen by electrocatalytic water decomposition in an acidic environment, and specifically relates to an iridium zinc ultrathin nanosheet material, a preparation method thereof, and use thereof as an oxygen evolution electrode material. Background Art
[0002] With the continuous development of economy, the global demand for energy is constantly expanding, and the energy crisis and environmental problems are becoming increasingly prominent. In this context, the development of clean and sustainable energy is imminent. Hydrogen energy has the characteristics of high energy density (~120MJ / kg), environmental friendliness and sustainability, and is an ideal energy source for solving global environmental problems and energy needs. Traditional fossil fuel hydrogen production has the problems of low hydrogen purity and environmental pollution, while clean, safe and efficient water splitting hydrogen production is a promising hydrogen production technology. However, the slow four-electron transfer in the oxygen evolution reaction is a huge challenge to water splitting. Its reaction kinetics are relatively slow and it is the rate-limiting step in the water splitting reaction process. Proton exchange membrane water electrolysis (PEMWE) is considered to be one of the most efficient, stable and reliable hydrogen production technologies. It has the advantages of high hydrogen purity, high maximum allowable current density, high conversion rate and large hydrogen production; however, stable electrolysis and low electrolyzer voltage in an acidic environment usually require Ir-based precious metal catalysts to achieve, which increases the cost of hydrogen production. Therefore, developing high-quality, active and stable Ir-based anodic oxygen evolution electrocatalysts in acidic media is crucial to promote the industrial application of PEMWE.
[0003] Transition metal modification is a method that can simultaneously reduce the noble metal loading and increase the IrO xA simple and effective strategy to improve the performance of acidic oxygen evolution. Due to the strong electronic interaction in atomic heterostructures, it helps to regulate the electronic structure of Ir active sites and reduce the electron density, thereby optimizing the adsorption and desorption energy of reaction intermediates on the surface of active sites, reducing the reaction energy barrier and improving the kinetics of oxygen evolution reaction (OER). In addition, there are abundant adsorption sites for water or hydroxide molecules in the amorphous phase, and the crystalline phase has good conductivity and stability, which can drive the transfer of electrons to the adsorbed molecules and promote the charge transfer between the adsorbed species and the catalyst surface. The synergistic effect between the crystalline phase and the amorphous phase at the heterointerface can also accelerate the originally slow OER kinetics. Therefore, it is expected to further improve the OER performance by constructing atomic heterostructures and crystalline / amorphous phase interfaces through non-precious metal modification. Metallic Zn is non-toxic, cheap and readily available, but its acidic OER activity and stability are poor; the Lu prepared by Zn doping in the literature (Tuning the hybridization state of Ir-O to improve the OER activity and stability of iridium pyrochlore via Zndoping, Applied Surface Science, 2022.) 1.8 Zn 0.2 Ir 2 O 7 Nanoparticles at 10 mA cm -2 The oxygen evolution overpotential at the current density was 331 mV, and the mass activity was only 135.32 A g at a voltage of 1.58 V vs. RHE. -1 Ir , at 10 mA cm -2 Its oxygen evolution stability is only 11 hours at a current density of 1.37 W, although the activity is significantly improved after doping with Zn (Lu 2 Ir 2 O 7 The mass activity is 108.75A g -1 Ir ), but its oxygen evolution activity and stability are still poor, and the stable operation time is short.
[0004] The present invention is proposed for this purpose. Summary of the invention
[0005] In order to solve the problem of expensive and poor performance of existing water splitting anode oxygen evolution electrode materials, the present invention provides an iridium zinc ultrathin nanosheet material with high activity and excellent stability. The iridium zinc ultrathin nanosheet material prepared by the present invention is used for oxygen evolution electrode, and its oxygen evolution performance is significantly improved.
[0006] The technical solution of the present invention is as follows:
[0007] The first aspect of the present invention discloses an iridium zinc ultra-thin nanosheet material with high activity and excellent stability, wherein the thickness of the nanosheet is 5-20 nm.
[0008] Preferably, the atomic number ratio of Zn / Ir in the iridium-zinc ultra-thin nanosheet material is (11.5-4.9):1.
[0009] Preferably, the iridium zinc ultra-thin nanosheet material has an atomic heterostructure and a heterogeneous interface between a crystalline phase and an amorphous phase.
[0010] The second aspect of the present invention discloses a method for preparing the iridium zinc ultra-thin nanosheet material, comprising the following steps:
[0011] (1) dissolving a zinc precursor and 2-methylimidazole in methanol to obtain respective methanol solutions;
[0012] (2) mixing the two methanol solutions of step (1), separating, washing and drying to obtain a white solid;
[0013] (3) dispersing the white solid in ultrapure water to obtain a dispersion, adding the iridium precursor solution dropwise to the dispersion, mixing, separating, washing, and drying to obtain a light yellow solid;
[0014] (4) calcining the light yellow solid powder to obtain a gray-blue powder, which is the iridium zinc ultra-thin nanosheet material.
[0015] Preferably, the zinc precursor in step (1) is Zn(NO 3 ) 2 6H 2 O, the iridium precursor solution described in step (3) is a chloroiridic acid solution.
[0016] Preferably, the mixing temperature in step (2) is 25-35°C and the mixing time is 3-4 hours; the washing method is washing with methanol at least three times; and the drying temperature is 50-80°C.
[0017] Preferably, the mixing temperature in step (3) is 35-45°C and the mixing time is 10-12 hours; the washing method is washing with water and ethanol at least three times respectively; and the drying temperature is 50-80°C.
[0018] Preferably, the calcination temperature in step (4) is 380-450° C. and the calcination time is 4-5 hours.
[0019] The third aspect of the present invention discloses the use of the iridium zinc ultra-thin nanosheet material for oxygen evolution electrodes.
[0020] Beneficial effects of the present invention:
[0021] 1. The iridium-zinc metal oxide alloy material of the present invention has an ultrathin nanosheet structure with a thickness of 5-20 nm. When used for oxygen evolution electrodes, the ultrathin nanosheet structure can strengthen the interface contact between the catalyst and the electrolyte, which is beneficial to fully expose the active sites and increase the electrochemical active area.
[0022] 2. The heterostructure of Ir and Zn atoms formed in the iridium zinc ultra-thin nanosheet material of the present invention has strong electronic interaction, which helps to regulate the electronic structure of the Ir active site and reduce the electron density; when used in the oxygen evolution electrode, it optimizes the adsorption and desorption energy of the reaction intermediates on the surface of the active site, also reduces the reaction energy barrier and improves the oxygen evolution reaction kinetics, thereby being able to produce excellent electron transfer ability and rapid oxygen evolution reaction kinetics.
[0023] 3. The iridium zinc ultra-thin nanosheet material of the present invention has a heterogeneous structure of crystalline phase and amorphous phase. It has abundant heterogeneous interfaces between crystalline phase and amorphous phase, and produces an appropriate proportion of metal oxygen and hydroxyl oxygen content; there are abundant water or hydroxide molecule adsorption sites in the amorphous phase, and its surface hydroxyl groups are easily converted into electrophilic O I- species, which is conducive to nucleophilic attack by water molecules or hydroxyl ligands, promoting OO coupling to produce O 2 ; The crystalline phase has good conductivity and stability, which can drive the transfer of electrons to the adsorbed molecules and promote the charge transfer between the adsorbed species and the catalyst surface; when used in oxygen evolution electrodes, the synergistic effect of the two phases can accelerate the originally slow oxygen evolution reaction kinetics, which is conducive to obtaining suitable intermediate binding energy, thereby reducing the reaction energy barrier and improving catalytic activity.
[0024] 4. The iridium zinc ultra-thin nanosheet material of the present invention has excellent oxygen evolution performance. -2 At a current density of 2.5 wt %, the oxygen evolution overpotential is only 271 mV, which is lower than the 338 mV of iridium oxide and the oxygen evolution overpotential of zinc oxide (inactive); at the same time, the slope of the Tafel curve and the charge transfer resistance are also lower than those of iridium oxide, which shows excellent charge transfer ability and fast oxygen evolution reaction kinetics.
[0025] 5. The iridium zinc ultra-thin nanosheet material of the present invention has a stable structure and can withstand 10 mA cm -2 In the oxygen evolution stability test under current density, the activity did not significantly decay after running for 115 hours, which is significantly better than the Lu prepared by Zn doping reported in the literature. 1.8 Zn 0.2 Ir 2 O 7 Properties of nanoparticles.
[0026] 6. The preparation method of the iridium zinc ultra-thin nanosheet material of the present invention is a simple impregnation-calcination method. The present invention synthesizes a high-activity iridium zinc metal oxide alloy material having a crystalline phase / amorphous phase and an ultra-thin nanosheet structure for the first time. The preparation method of the present invention has a wide range of raw material sources and a simple synthesis path. Its high activity and strong stability are suitable for industrial proton exchange membrane water electrolyzers. The iridium zinc ultra-thin nanosheet material of the present invention and its preparation method are reported for the first time. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope image of the iridium zinc ultrathin nanosheet material prepared in Example 1 of the present invention.
[0028] Figure 2 This is a transmission electron microscope image of the iridium zinc ultrathin nanosheet material prepared in Example 1 of the present invention.
[0029] Figure 3 These are X-ray diffraction patterns of the iridium zinc ultrathin nanosheet material prepared in Example 1 of the present invention and the zinc oxide material prepared in Comparative Example 1.
[0030] Figure 4 This is the X-ray photoelectron spectrum of the iridium zinc ultrathin nanosheet material prepared in Example 1 of the present invention, the zinc oxide material prepared in Comparative Example 1, and the iridium oxide material in Comparative Example 2.
[0031] Figure 5 The oxygen evolution performance of the iridium zinc ultrathin nanosheet material prepared in Example 1 of the present invention, the zinc oxide material and the iridium oxide material in the comparative example: (a) polarization curve, (b) electrochemical impedance spectrum and (c) Tafel curve.
[0032] Figure 6 This is a test curve of oxygen evolution stability of the iridium zinc ultrathin nanosheet material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, preparation method and advantages of the present invention more clear, the present invention is further described below in conjunction with specific embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0034] Example 1: Preparation of iridium zinc ultrathin nanosheet material.
[0035] (1) 4.58 g Zn(NO 3 ) 2 6H 2 O and 5.50 g of 2-methylimidazole were dissolved in 200 mL of methanol to obtain their respective methanol solutions;
[0036] (2) Add 2-methylimidazole methanol solution to the stirred Zn(NO3 ) 2 The mixture was stirred in methanol solution at a constant temperature of 30°C for 3 hours. The white solid was separated by centrifugation, washed three times with methanol, and dried in vacuum at 60°C to obtain a white solid powder of ZIF-8;
[0037] (3) Weigh 100 mg of ZIF-8 white powder, disperse it in 60 mL of ultrapure water and sonicate for 1 hour; pipette 0.5 mL of 20 g / L chloroiridic acid solution into a beaker and dilute it with 10 mL of water; then add the chloroiridic acid solution dropwise to the stirred ZIF-8 dispersion, wash the beaker with 10 mL of water and add it dropwise to the ZIF-8 dispersion, and stir continuously for 12 hours at a constant temperature of 40°C; then centrifuge, wash three times with water and ethanol in sequence, and vacuum dry at a constant temperature of 60°C to obtain a light yellow solid powder;
[0038] (4) Place the light yellow solid powder in a muffle furnace at 5°C min -1 The obtained product was heated to 400 °C at a rate of 1000 °C and calcined for 4 h, and then naturally annealed to room temperature to obtain a gray-blue powder.
[0039] Comparative Example 1: Preparation of zinc oxide material.
[0040] (1) 4.58 g Zn(NO 3 ) 2 6H 2 O and 5.50 g 2-methylimidazole were dissolved in 200 mL methanol;
[0041] (2) Add 2-methylimidazole methanol solution to the stirred Zn(NO 3 ) 2 The mixture was stirred continuously for 3 hours at a constant temperature of 30°C in a methanol solution; a white solid was separated by centrifugation, washed three times with methanol, and dried in a vacuum at 60°C to obtain a white solid powder of ZIF-8;
[0042] (3) Place the white solid powder of ZIF-8 in a muffle furnace and heat it at 5°C min -1 The zinc oxide was obtained by heating the sample to 450°C at a rate of 1000 ℃ and calcining it for 4 hours, and then annealing it to room temperature. The zinc oxide was used to replace the iridium zinc ultrathin nanosheets to prepare the anode oxygen evolution working electrode.
[0043] Comparative Example 2: Commercially available iridium oxide material.
[0044] Commercially available iridium oxide was used instead of iridium zinc ultrathin nanosheets to prepare the anodic oxygen evolution working electrode.
[0045] Preparation of the working electrode for the anode oxygen evolution reaction: The materials obtained in the examples and comparative examples were made into ink and drop-coated on the glassy carbon electrode to prepare the working electrode. The steps are as follows: first, 4 mg of the solid powder obtained in the examples and comparative examples and 1 mg of carbon nanotubes were dissolved in a mixed solution consisting of 625.0 μL of ultrapure water, 312.5 μL of isopropanol and 62.5 μL of Nafion, and the mixed solution was ultrasonically treated for 1 hour to obtain a catalyst ink; secondly, 3.5 μL of the catalyst ink was drop-coated on the glassy carbon electrode and dried at room temperature to obtain 0.2 mg cm -2 of catalyst loading.
[0046] Oxygen evolution reaction performance test: saturated calomel electrode and platinum mesh were used as reference electrode and counter electrode respectively in 40mL, 0.1M HClO 4 The oxygen evolution performance was evaluated in an electrolyte solution at a constant temperature of 30°C. The oxygen evolution reaction activity was evaluated in the potential range of 1.2-1.8 V vs RHE at a rate of 2 mV s -1 Linear voltammetry was performed at a scan rate of 1.50 V vs RHE and a scan frequency range of 100 kHz-0.05 Hz for oxygen evolution electrochemical impedance spectroscopy. The current density was 10 mA cm -2 A long-term constant current stability test was performed to obtain a voltage-time (Et) curve.
[0047] Figure 1 This is a scanning electron microscope image of the iridium zinc ultrathin nanosheet material prepared in Example 1. Figure 1 It can be seen that the iridium-zinc metal oxide alloy prepared in Example 1 has an ultra-thin nanosheet structure, and the thickness of the nanosheet is about 10 nm.
[0048] Figure 2 This is a transmission electron microscope image of the iridium zinc ultrathin nanosheet material prepared in Example 1. Figure 2 (a) It can be seen that the nanosheet structure of the iridium-zinc metal oxide alloy prepared in Example 1; Figure 2 (b) It can be found that the transmission electron microscopy image under high magnification clearly shows lattice fringes with lattice spacings of 0.249nm, 0.198nm and 0.166nm, which are slightly larger than the lattice spacings of the (101), (102) and (110) crystal planes of ZnO (0.247nm, 0.191nm, 0.162nm), confirming that Ir atoms are successfully embedded in ZnO crystals to form iridium-zinc metal oxide alloys; in addition, an amorphous structure is observed in close proximity to the crystal, resulting in a rich heterogeneous interface of crystalline and amorphous phases (white dotted lines in the figure).
[0049] Figure 3The X-ray diffraction patterns of the iridium zinc ultrathin nanosheet material prepared in Example 1 and the zinc oxide material prepared in Comparative Example 1; Figure 3 (a) It can be observed that the iridium zinc ultrathin nanosheets obtained in Example 1 and the zinc oxide obtained in Comparative Example 1 both exhibit eight significant crystallization peaks of ZnO, which are respectively attributed to the (110), (002), (101), (102), (110), (103), (103) and (440) crystal planes of ZnO, and no significant IrO 2 Crystallization peak; Figure 3 (b) It can be found that relative to the ZnO crystallization peak, the corresponding crystallization peak in the iridium-zinc ultrathin nanosheet obtained in Example 1 is shifted to a low angle. This is caused by the embedding of Ir atoms into the ZnO lattice, indicating that Ir atoms have been successfully embedded into the ZnO lattice to form an iridium-zinc metal oxide alloy.
[0050] Figure 4 X-ray photoelectron spectra of the iridium zinc ultrathin nanosheet material prepared in Example 1, the zinc oxide prepared in Comparative Example 1, and the iridium oxide material prepared in Comparative Example 2; Figure 4 (a) It can be seen that compared with the commercially available iridium oxide material, the Ir 4f peak position of the iridium zinc ultrathin nanosheet of the present invention shifts to a higher binding energy, and Figure 4 (b) It can be seen that relative to the zinc oxide material, the Zn 2p peak position of the iridium zinc ultrathin nanosheet of the present invention moves negatively to a lower binding energy; this indicates that electrons in the iridium zinc ultrathin nanosheet material have transferred from Ir to Zn atoms, resulting in a higher electron density at the Zn site and a lower electron density at the Ir site; this confirms that a strong electronic interaction is generated between Ir and Zn atoms, and regulates the electronic structure of the Ir active site.
[0051] Figure 5 The oxygen evolution performance curves of the iridium-zinc metal oxide alloy material prepared in Example 1, the zinc oxide material prepared in Comparative Example 1, and the iridium oxide material prepared in Comparative Example 2 are shown in FIG. Figure 5 (a) It can be seen that the iridium zinc ultrathin nanosheet material prepared in Example 1 has a high conductivity when reaching 10 mA cm -2 The voltage required for the current density is only 1.501V, and the overpotential is only 271mV (the theoretical voltage of oxygen evolution is 1.23V), which is lower than iridium oxide (1.568V, overpotential is 338mV) and zinc oxide (inactive), showing excellent oxygen evolution activity; Figure 5 (b) and Figure 5 (c) shows that the iridium zinc ultrathin nanosheet material prepared by the present invention also has the smallest Tafel slope and charge transfer resistance, which are as low as 35.4 mV dec. -1 With 5.06Ωcm 2 , much smaller than iridium oxide (73.2mVdec-1 , 52.95Ωcm 2 ), demonstrating its superior charge transfer ability, rapid oxygen evolution reaction kinetics and higher catalytic activity. Therefore, the oxygen evolution performance of the iridium zinc ultra-thin nanosheet material prepared in Example 1 is far superior to that of the iridium oxide and zinc oxide materials in the comparative example.
[0052] Figure 6 This is the stability test curve of the iridium zinc ultra-thin nanosheet material prepared in Example 1. Figure 6 It can be seen that its activity does not decrease significantly after 115 hours of oxygen evolution electrolysis, indicating its excellent stability in the water decomposition process. Therefore, the iridium zinc ultra-thin nanosheet material prepared in Example 1 of the present invention achieves a balance between high activity and excellent stability, and is expected to become a cheap and efficient candidate material for acidic oxygen evolution reaction.
[0053] Example 2
[0054] (1) The preparation of ZIF-8 white solid powder was the same as steps (1) and (2) of Example 1;
[0055] (2) Weigh 100 mg of ZIF-8 white powder and disperse it in 60 mL of ultrapure water by ultrasonication for 1 hour, transfer 0.25 mL of 20 g / L chloroiridic acid solution into a beaker, and add 10 mL of water to dilute; then add the chloroiridic acid solution dropwise to the stirred ZIF-8 dispersion, wash the beaker with 10 mL of water and add dropwise to the mixture, and stir continuously at a constant temperature of 40° C. for 12 hours; then centrifuge to separate the light yellow solid, wash it three times with water and ethanol in sequence, and vacuum dry it at a constant temperature of 60° C. to obtain a light yellow solid powder;
[0056] (3) The method for preparing gray-blue iridium-zinc metal oxide alloy powder by calcining light yellow solid powder is the same as step (4) of Example 1.
[0057] The acidic oxygen evolution activity of the iridium zinc ultrathin nanosheet material obtained in Example 2 is as follows: -2 The overpotential at the current density is 296 mV and the charge transfer resistance is 11.31 Ω cm 2 , Tafel slope is 55.8mV dec -1 .
[0058] Example 3
[0059] (1) The preparation of ZIF-8 white solid powder was the same as steps (1) and (2) of Example 1.
[0060] (2) Weigh 100 mg of ZIF-8 white powder and disperse it in 60 mL of ultrapure water by ultrasonication for 1 hour, transfer 1.00 mL of 20 g / L chloroiridic acid solution into a beaker, and add 10 mL of water to dilute; then add the chloroiridic acid solution dropwise to the stirred ZIF-8 dispersion, wash the beaker with 10 mL of water and add dropwise to the mixture, and stir continuously at a constant temperature of 40°C for 12 hours; then centrifuge to separate the light yellow solid, wash it three times with water and ethanol in sequence, and vacuum dry it at a constant temperature of 60°C to obtain a light yellow solid powder.
[0061] (3) The method for preparing gray-blue iridium-zinc metal oxide alloy powder by calcining light yellow solid powder is the same as step (4) of Example 1.
[0062] The acidic oxygen evolution activity of the iridium zinc ultrathin nanosheet material obtained in Example 3 is as follows: -2 The overpotential at the current density is 279mV and the charge transfer resistance is 6.22Ωcm 2 , Tafel slope is 47.2mV dec -1 .
[0063] The above embodiments are not limitations of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by those skilled in the art within the essential scope of the present invention also fall within the protection scope of the present invention.
Claims
1. An iridium zinc ultrathin nanosheet material, characterized in that: The thickness of the nanosheets is 5-20 nm.
2. The iridium zinc ultrathin nanosheet material according to claim 1, characterized in that: The atomic number ratio of Zn / Ir in the iridium-zinc ultra-thin nanosheet material is (11.5-4.9):
1.
3. The iridium zinc ultra-thin nanosheet material according to claim 1, characterized in that: The iridium zinc ultra-thin nanosheet material has an atomic heterogeneous structure and a heterogeneous interface between a crystalline phase and an amorphous phase.
4. The method for preparing the iridium zinc ultrathin nanosheet material according to claim 1, characterized in that: The following steps are involved: (1) dissolving a zinc precursor and 2-methylimidazole in methanol to obtain respective methanol solutions; (2) mixing the two methanol solutions of step (1), separating, washing and drying to obtain a white solid; (3) dispersing the white solid in water to obtain a dispersion, adding the iridium precursor solution dropwise to the dispersion, mixing, separating, washing, and drying to obtain a light yellow solid; (4) calcining the light yellow solid powder to obtain a gray-blue powder, which is the iridium zinc ultra-thin nanosheet material.
5. The preparation method according to claim 4, characterized in that: The zinc precursor described in step (1) is Zn(NO3)2·6H2O, and the iridium precursor solution described in step (3) is chloroiridic acid solution.
6. The preparation method according to claim 4, characterized in that: In step (2), the mixing temperature is 25-35° C. and the mixing time is 3-4 hours; the washing method is washing with methanol at least three times; and the drying temperature is 50-80° C.
7. The preparation method according to claim 4, characterized in that: In step (3), the mixing temperature is 35-45° C. and the time is 10-12 hours; the washing method is to use water and ethanol to wash at least three times respectively; and the drying temperature is 50-80° C.
8. The preparation method according to claim 4, characterized in that: The calcination temperature in step (4) is 380-450° C. and the calcination time is 4-5 hours.
9. Use of the iridium zinc ultrathin nanosheet material according to any one of claims 1 to 3 in an oxygen evolution electrode.
Citation Information
Patent Citations
Ultrathin iridium-based nanosheet catalyst as well as preparation method and application thereof
CN115807241A
Iridium-cobalt nano-alloy as well as preparation method and application thereof
CN116815229A
Iridium / ruthenium-based anode catalyst for water electrolysis, method for preparing same, and water electrolysis device using same
US20240263324A1